International Conference on Science and Applied Science (Engineering and Educational Science) 2016 (ICSAS 2016) - - - (Universitas Sebelas Maret, 2017)
Syariah Hotel Solo Surakarta, Indonesia 19 November 2016 PrefaceInternational Conference on Science and Applied Science (Engineering and Educational Science) 2016 (ICSAS 2016) was held at the Syariah Hotel Solo, Surakarta, Indonesia on 19 November 2016. The ICSAS 2016 conference is aimed to bring together scholars, leading researchers and experts from diverse backgrounds and applications areas in Science. Special emphasis is placed on promoting interaction between the science theoretical, experimental, and education sciences, engineering so that a high level exchange in new and emerging areas within Mathematics, Chemistry, Physics, and Biology, all areas of sciences and applied mathematics and sciences is achieved.in ICSAS 2016, there are five keynote speaker from three different countries, while participants come from five different countries and divided in five parallel sessions All the paper that has been accepted for presentation in ICSAS 2016 are published online in Journal of Physics: Conference Series by IOP Publishing or in conference proceedings. The papers that do not qualify unacceptable in IOP publishing are published in conference proceedings International Journal of Science and Applied Science: Conference Series by Sebelas Maret University.It is an honour to present this volume of International Journal of Science and Applied Science: Conference Series and we deeply thank the authors for their enthusiastic and high-grade contribution. We would like to express our sincere gratitude to all in the Programming Committee who have reviewed the papers and developed a very interesting Conference Program, as well as thanking the invited and plenary speakers. Finally, we would like to thank the conference chairman, the members of the steering committee, the organizing committee, the organizing secretariat and the financial support from the Sebelas Maret University that allowed ICSAS 2016 to be a success.The Editor of the ICSAS 2016 Proceedings:Prof. Dra. Suparmi, M.A.,Ph.D Dr. Fuad Anwar, S.Si.,M.Si